Peranan Badan Permusyawaratan Desa dalam Menampung dan Menyalurkan Aspirasi Masyarakat di Desa Sumerta Kelod - I Made Prama Wianta; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2022)
The emergence of the Village Consultative Body (BPD) gives its own color to democratic life, because the main purpose of establishing the Village Consultative Body is to create democracy in the village. In this case, the Village Consultative Body has the function of establishing Village Regulations. This study aims to determine the role of the Village Consultative Body (BPD) when accommodating and channeling community aspirations. Using the empirical method, we can formulate the formulation of the problem, namely: (1) What is the role of the Village Consultative Body in accommodating and channeling the aspirations of the community in Sumerta Kelod village (2) What are the constraints of the Village Consultative Body in accommodating and channeling community aspirations in Sumerta Kelod village, and this research using empirical methods. The conclusion in this study in outline is that the function that has been carried out by the Sumerta Kelod Village Consultative Body (BPD) is currently going well and has been running according to the procedure, although there are still some obstacles, namely, lack of coordination, lack of understanding of the Sumerta Kelod Village community with limitations. -restrictions on the duties and authority of the BPD, and there are still very few discussion forums with other villages.